Bedside ocular ultrasonography for diagnosing increased intracranial pressure in patients with leptomeningeal metastases from non‐small‐cell lung cancer. (4th December 2022) - Jiang, Cheng; Lin, Yongjuan; Li, Huiying; Xie, Yu; Yu, Tingting; Feng, Jingyu; Huang, Mingmin; Guo, Aibin; Shen, Haiyun; Zhang, YiDan; Yin, Zhenyu
Abstract: Objectives: To explore the diagnostic accuracy of ultrasound measurement of optic nerve sheath diameter (ONSD) and optic disc height (ODH) in detecting intracranial hypertension in non‐small‐cell lung cancer (NSCLC) patients with leptomeningeal metastases (LM). Methods: Seventy‐two patients with NSCLC‐LM and 65 patients with NSCLC were enrolled. The ONSD, ODH, eyeball transverse diameter (ETD), and eyeball vertical diameter (EVD) were measured by ultrasound. Subsequently, lumbar puncture was performed in NSCLC‐LM patients to measure cerebrospinal fluid pressure (CSFP), and intrathecal chemotherapy was regularly implemented. Pearson's correlation analysis was used to analyze the relationship between CSFP and ultrasound findings. The diagnostic accuracy of ONSD, ODH, and combined ONSD and ODH was evaluated by receiver operating characteristic (ROC) curve analysis and the corresponding area under the ROC curve (AUC). Results: The ONSD, ODH, ONSD/ETD, and ONSD/EVD values were higher in the NSCLC‐LM group (all p  < 0.05). The ONSD, ODH, ONSD/ETD, and ONSD/EVD values were all elevated in the abnormally elevated CSFP group (all p  < 0.05). ONSD, ODH, ONSD/ETD, and ONSD/EVD were positively correlated with CSFP ( r  = 0.531, 0.383, 0.534, and 0.535, all p  < 0.0001). The AUCs for ONSD, ODH, ONSD/ETD, and ONSD/EVD to detect CSFP >280 mmH2O were 0.787 (95% CI: 0.64–0.93, sensitivity 68.75%, specificity 91.07%), 0.885 (95% CI: 0.81–0.96, sensitivity 100%, specificity 69.64%), 0.765 (95% CI: 0.64–0.89, sensitivity 81.25%, specificity 64.29%), and 0.788 (95% CI: 0.64–0.93, sensitivity 56.25%, specificity 91.07%), respectively. When ONSD was combined with ODH, the AUC was 0.913 (95% CI: 0.83–0.99, sensitivity 87.85%, specificity 85.70%). Furthermore, intrathecal chemotherapy was associated with a downtrend in CSFP and ultrasound findings. Conclusion: There are important advantages of using bedside ultrasonography for detecting elevated CSFP in NSCLC‐LM patients. Further research should be performed to evaluate the clinical significance of an enlarged ONSD and increased ODH in NSCLC‐LM. Abstract : Bedside ocular ultrasonography is a noninvasive, bedside and easy‐to‐use way for detecting increased intracranial pressure in patients with leptomeningeal metastases from non‐small‐cell lung cancer. The measurement of combined ONSD and ODH may be a promising technique to detect elevated CSF pressure..